Orang Tua Dan Anak : Sinergi Dalam Proses Pembelajaran Anak Usia Dini - Devi Marganing Tyas; Yulyanti Minarsih; Ananda Saadatul Maulidia; Bramusti Aji Prabowo; Vania Zaimatun Nisa (KOLONI, 2024)
: This study aims to explore parental involvement in supporting early childhood learning processes, focusing on forms of involvement, influencing factors, and their impacts on children’s development. The background of this research is based on the importance of education during the golden age (0–6 years) in shaping the foundation of children’s cognitive, socio-emotional, and moral development. The method used is a descriptive qualitative approach with 3 parents of kindergarten students in Klaten as research subjects. Data were collected through in-depth interviews, observations, and documentation, analyzed using triangulation techniques to ensure validity. The findings reveal that parental involvement, such as assisting children in learning, providing emotional support, and maintaining consistency in learning methods at home, significantly impacts children’s academic abilities, social-emotional skills, and learning motivation. Major challenges identified include parents' busy schedules, lack of understanding of their roles, and the perception that education is solely the school’s responsibility. The study concludes that synergy between family and school is crucial to optimize early childhood development. This research offers practical recommendations to strengthen parental involvement through parenting training and collaborative programs with schools.